Adaptation of a gasoline-fueled conventional engine into a purified biogas-fueled engine for power generation - Hernandez, Noel M.; Villanueva, Eliseo P. (2010)
A Kubota AE3500 spark ignition engine was modified for a purified biogas operation. Provision was done for the inlet of the purified biogas, adjustment of the spark plug gap setting and assessment of the ignition timing. The purification process of the biogas was also done by attaching two drum purification system arranged in series into an existing semi-continuous biogas digester. One drum is for the removal of CO2 and the other removal of H2S. The purified biogas-fueled engine was tested for smoothness in operation, overall thermal efficiency and specific fuel consumption. Tests were conducted at different loads, rpm fuel inlet pressure and air fuel ratio. Gas analyses at the inlet and exhaust were conducted in every experimental run. Results indicate that with proper engine modification and biogas purification, a purified biogas is a very good engine fuel alternative.
Keywords: Biogas; Biogas purification; Alternative fuel; Conventional engine modification